STRATEGI PENGEMBANGAN DAYA SAING LULUSAN TEKNIK INDUSTRI FAKULTAS TEKNIK: Studi Kasus PTS X di Kopertis Wilayah II - Burhan Nudin (Universitas Mercu Buana, 2017)
The high level of competition in the world of education and limited available employment requires every university to continuously improve the quality of its education in order to be able to produce qualified graduates in various levels and fields of science. Therefore, a competitiveness development strategy is needed for industrial engineering graduates in engineering faculty, due to lack of company understanding about industrial engineering profession and some conditions about the scope of work of industrial engineering graduates. In this research data analysis using SWOT, EFI Matrix, EFE and IE. The result of this research can be seen that the design of the competitiveness development strategy of industrial engineering graduates of Faculty of Engineering PTS X is in cell five (V) and from EFI and EFE matrix processing calculation, the average score is 2,616 and 2,909. Strategies that can be done there are 78 points for development, in this study based on SWOT analysis needed for development seen from SO, WO, ST, WT.